(untitled) (Per Musi, 2014)
Style study on the music of American composer and pianist Billy Strayhorn who became Duke Ellington’s right arm and alter ego. It discusses the unique compositional collaboration between the two giants of jazz and the question of authorship in the Duke Ellington Orchestra repertory. It includes a historical context of Strayhorn’s musical background and his works. The analysis of 19 selected works of Billy Strayhorn reveals traits related to style/tempo, time signature, tonality, form, length, harmonic chord pace and harmonic language and some other relevant details.